Diagnosis and management of multiple salivary gland anomalies: A Case report - Hamasaki, Jean Teruo; Trentin, Carolina Muniz; Pascoto, Gabriela Robaskewicz; Araujo, Melissa Rodrigues de (Journal of Oral Diagnosis, 2022)
Anatomical anomalies in the salivary glands, such as ductal ectasia and stenosis, are rare and can be idiopathic, congenital, or acquired. The diagnosis of these anomalies is based on imaging examinations and is sometimes challenging. A 65-year-old female patient complained of a recurrent volume increase in the right preauricular region for 43 years. The swelling was exacerbated during the periprandial period. Physical examination with palpation revealed a flaccid swelling. Aspiration showed clear liquid compatible with saliva. Ultrasonography and magnetic resonance (MR) sialography showed changes in ductal anatomy and sialocele. MR sialography allowed the diagnosis of sialocele secondary to idiopathic duct anomalies, ectasia, and strictures in the parotid ducts. The treatment was sialoendoscopy. The patient presented a good clinical evolution with a significant reduction in swelling in the preauricular region due to less saliva accumulation. Sialoendoscopy is an effective method for the diagnosis and treatment of major salivary gland anomalies.